Measuring Tourism Flows: The Asian case - Ibragimov, Khusen; Perles-Ribes , José; Ramón-Rodríguez, Ana (Turizam, 2021)
This article provides a comprehensive analysis of the determinants of inbound tourism to Asia. The research will focus on a combination of economic and non-economic variables applying a gravity model to a panel of 46 Asian countries of destination and 197 countries of origin for the period 1995-2016. The findings show that moderate levels of corruption, good quality institutions, a shared common language, religion, and border could boost international tourist arrivals to Asia. Politically unstable Asian destinations are most likely to lose tourist arrivals from Europe. Good quality institutions, strong colonial ties, language closeness, common religion and borders increase the number of international tourist arrivals to Asia from Europe, Africa North & South America and the Pacific. A surge in rainfall and temperature would not change the willingness of tourists to travel to Asia from Europe.